KEMAUAN MENINGKATKAN KEBERADAAN SISTEM INFORMASI SEBAGAI FUNGSI KEBERHASILAN SISTEM - Sasongko, Noer (Benefit: Jurnal Manajemen dan Bisnis, 2005)
This research develops a theory to select measurement criterion related to function successfulness ofinformation system. The criterion represents intent of existence of information system (intent of systemdevelopment) because of successfulness previous information system. Generalized cost/benefit measure isused to compile hypothesis. This matter test validity decision of system development after perceivingsuccessfulness of information system. Result of from this research indicate that the information quality can function as base to user ofsystem to develop system, and usefulness system depict a valid measure that it can function to evaluateeligibility from an alternative of project system development. And also the cost from system developmentproject shows influence significance to intent of system development. Become result of this research showrelation between third independent variable to intent of system development.